Health-related quality of life of adolescents living with HIV treated at the HIV Clinic at the National Institute of Pediatrics at Mexico City. (1st June 2022) - Montoya Moya, D.B.; Molina, D.; Ordoñez Ortega, J.
Abstract : Introduction: ATR for children has successfully increase survival to adolescence. Health-related quality of life (HRQoL) is relevant to evaluate the impact of the disease on well-being in adolescents living with HIV (ALH). Kidscreen-52 questionnaire is validated in mexican adolescents to measure HRQoL Objectives: To evaluate health related quality of life in a sample of 22 mexican ALH Methods: A sample of ALH in treatment at the HIV Clinic during 2021, were evaluated with Kidscreen-52 by a child psychiatrist. Statistics included non parametric tests and Cohen "d" and "r" size effect to compare T means between ALH and Kidscreen-52 standardized scores. Results: Mean age:14.4+2.5. Gender: 11(50%)boys, 11(50%)girls. ALH showed significantly lower scores in all domains. Girls reported lower scores in physical well-being(p=0.047) and autonomy (p=0.023). Orphan ALH had lower scores in mood and emotions (p=0.021) Conclusions: - HRQoL were significantly lower in ALH. -Girls showed significantly lower scores in physical well-being and autonomy. - ALH orphans showed significantly lower scores in mood and emotions domain Disclosure: No significant relationships.